Effect of salinity, temperature, light intensity and photoperiod on reproduction, larval development and life cycle of cyclopoid copepod, Oithona simplex (Farran, 1913) - Mat Noor, Nur Syuhada; Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Kamarudin, Mohd Salleh (Science Alert, 2018)
Background and Objective: Copepods are being used widely as live feed in aquaculture industry particularly for larval rearing of fish and crustacean. Several marine copepods have been cultured successfully before but the numbers of species documented is still limited. Cyclopoid copepod, Oithona simplex is readily available in the Malaysian coastal waters and their high abundance is observed in the coastal waters of Port Dickson, Malaysia. It is targeted as a potential live food for larval rearing of marine fish species. The present study was conducted to determine the effect of environmental parameters viz. salinity, temperature, light intensity and photoperiod on the reproductive cycle of cyclopoid copepod, Oithona simplex under laboratory condition. Materials and Methods: Four different salinity levels (20, 25, 30 and 35 ppt), three different temperatures set up (25, 30 and 35°C), three light intensities expose (5, 20, 35 μmol m–2 sec–1) and three different photoperiod phases (12 h light (L):12 h dark (D), 1 h (L):23 h (D), 24 h (L):0 h (D) were adopted during this experiment. Results were subjected to one-way ANOVA. Results: The results showed that the optimum salinity was recorded at 30 ppt for the highest production of off springs. Similar highest production was found at 35°C temperature setup. The optimum light intensity expose was under 5 μmol m–2 sec–1 and this was reflected by the increase in reproductive activity and decreased in development period. Subsequently, 12 h light:12 h dark treatment resulted in the highest reproduction process. Conclusion: It could be recommended that optimal environmental condition which comprised of 30 ppt salinity, 35°C temperature, 5 μmol m–2 sec–1 light intensity and alternate 12 h light and dark photoperiod is required for culturing of O. simplex in captivity. This is the first attempt to breed and mass production in controlled environment. The information gathered from the experiment could be helpful to produce a mass culture of O. simplex indoor for the purpose of live food supply in the hatchery.